Experimental and model study for fluoride removal by thermally activated sepiolite - Lee, Jae In; Hong, Seung Hee; Lee, Chang Gu; Park, Seong Jik (Chemosphere, 2020)
The present investigation demonstrates the preparation of thermally activated sepiolite for effective removal of fluoride via adsorption from an aqueous solution. The thermal treatments on sepiolite were conducted at different temperatures (300–950 °C) for 4 h in an N2 atmosphere, and the thermally activated sepiolite was characterized using a field emission scanning electron microscope (FESEM), X-ray diffractometry (XRD), X-ray fluorescence (XRF), a differential scanning calorimetry-thermogravimetric analyzer (DSC-TGA), and a surface area analyzer. Sepiolite that was treated at 950 °C was shown to have a higher fluoride removal efficiency than other temperatures. The fluoride removal was evaluated under different experimental conditions such as solution pH, adsorbent dose, reaction time, initial concentration, temperature, presence of co-existing ions, and reuses. The kinetic and equilibrium adsorption results were well described by the pseudo-second-order kinetic model and Langmuir isotherm, respectively, and adsorption of fluoride onto thermally activated sepiolite was endothermic and spontaneous in nature. The Langmuir maximum adsorption capacity (169.95 mg/g) was superior to the literature value. The thermally activated sepiolite was also effective in a continuous flow system for treating fluoride. Thus, this thermally activated sepiolite is expected to be used as an effective adsorbent for the removal of fluoride in water.
Keywords: Adsorption model; Batch experiments; Column experiments; Fluoride adsorptions; Thermally activated; Adsorption; Fluorides; Hydrogen-Ion Concentration; Kinetics; Magnesium Silicates; Models, Chemical; Spectrometry, X-Ray Emission; Thermodynamics; Thermogravimetry; Water Pollutants, Chemical; Water Purification; X-Ray Diffraction; Adsorption models; Batch experiments; Column experiments; Fluoride adsorption; thermally activated sepiolite